Impact of Terrorism On Human Rights - Brat Dash, Sidhya; Pattnaik, Sibasis (International Journal of Psychosocial Rehabilitation, 2025)
The tug of war between human rights and terrorism is becoming a question of global concern. Based on the different circumstances, however, the type of terrorism is quite different. Human Rights claims arise where terrorism violates the individual's minimum basic rights. The word "human rights" and "terrorism" is therefore synonymous. National and international terrorist groups in India are actively and threateningly active, damaging local property, killing innocent people. To monitor this hazard, the state has restricted physical resources. On the other hand, the terrorists posed a major threat to the country's internal security. Terrorism is an old problem, with new challenges. It has had a drastic impact on the world economy and the life of people. It is a plague on mankind. There is a strong correlation between human rights and terrorism. Terrorism is known to have existed, in one form on the other at several stages in the recorded history in almost all parts of the world after the9/11 attacks on the world trade centre in united states and the December 13, 2001 attacks on the Indian parliament and November 26,2008 attack in Mumbai, terrorism assumed new dimension and has come to threaten the very foundation of modern civilized society. India is not unfamiliar with terrorism. It's been a long-standing militant sufferer, whether in the North-East, Punjab, or Jammu & Kashmir. Moreover, however, terrorism has spread to other parts of the world since the last half a decade.